Non-Abelian gauge field optics - Yuntian Chen (Nature Portfolio, 2019)
In optics, schemes have been proposed to realize synthetic gauge fields, but are restricted to the Abelian type. Here, the authors demonstrate synthetic SU(2) non-Abelian gauge fields in anisotropic media, which allows the study of novel optical phenomena not found in Abelian synthetic gauge field systems.